Karakteristik Hubungan Muhammadiyah dan NU dalam Menggunakan Hisab dan Rukyat - Azhari, Susiknan (Al-Jamiah: Journal of Islamic Studies, 2006)
This article studies the matter of á¸¥isÄb and ruâya, particularly conducted by the following two extremely well-known socio-religious organizations, NU and Muhammadiyah. The reason for this choice is that the two for most of Indonesian people is the symbol of difference, even, of dissension among its Muslims referring to the thought of lunar calendar in Indonesia. The choice and the usage of the two matters frequently take place to determine the beginning of Ramaá¸Än, ShawwÄl, and DhÅ«âl-á¸¤ijja in spite of the others. Therefore, it is necessary to deal with how the relation between NU and Muhammadiyah is due to the matters. To find out the answer for the inquiry theoretical framework developed by Ian G. Barbour i.e.: Conflict, Independent, Dialogue and Integration will be exercised.